The Psychometric Properties of the Grit-O Scale Within the Twente Region in Netherlands: An ICM-CFA vs. ESEM Approach - van Zyl, Llewellyn E.; Olckers, Chantal; Roll, Lara C. (Frontiers in Psychology, 2020)
The purpose of this study was to examine the psychometric properties (i.e. factorial validity, measurement invariance and reliability) of the Grit-Original scale (Grit-O) within the Netherlands. The Grit-O scale was subjected to a competing measurement modelling strategy that sequentially compared both independent cluster model confirmatory factor analytical- and exploratory structural equation modelling approaches. The results showed that both a two first order, bi-factor structure as well as a less restrictive two factor ESEM factorial structure best-fitted the data. The instrument showed to be reliable at both a lower- (Cronbach’s alpha) and upper-level (composite reliability) limit. However, measurement invariance between genders could only be established for the B-ICM-CFA model. Finally, concurrent validity was established through relating the GRIT-O to task performance. The linear use of the Grit-O scale should therefore carefully be considered.